Addressing NCDs through research and capacity building in LMICs: lessons learned from tobacco control - Rachel Sturke; Susan Vorkoper; Kalina Duncan; Marya Levintova; Mark Parascondola (Taylor & Francis Group, 2016)
Confronting the global non-communicable diseases (NCDs) crisis requires a critical mass of scientists who are well versed in regional health problems and understand the cultural, social, economic, and political contexts that influence the effectiveness of interventions. Investments in global NCD research must be accompanied by contributions to local research capacity. The National Institutes of Health (NIH) and the Fogarty International Center have a long-standing commitment to supporting research capacity building and addressing the growing burden of NCDs in low- and middle-income countries. One program in particular, the NIH International Tobacco and Health Research and Capacity Building Program (TOBAC program), offers an important model for conducting research and building research capacity simultaneously. This article describes the lessons learned from this unique funding model and demonstrates how a relatively modest investment can make important contributions to scientific evidence and capacity building that could inform ongoing and future efforts to tackle the global burden of NCDs.